DEFENSE MECHANISM OF RIZWAN KHAN IN MY NAME IS KHAN MOVIE (2010) DIRECTED BY KARAN JOHAR: A PSYCHOANALYTIC APPROACH - SUPRAPTO , GUSHINTA EKAWATI (2011)
The problem statement of the study is to unravel how the defense My Name Is Khan. the objective of the study are to analyze the structural element of the film and analyze the character Sigmund Freud on psychoanalytic approach. This study is descriptive qualitative research. The object of the study is My Name Is Khan movie directed by Karan Johar. Data sources are divided into two namely primary and secondary data source. The data source is the movie itself and secondary data is the other sources related to the analysis. The techniques of data collection are observation and library research. The technique of data analysis is descriptive analysis. The result of the research shows that the problems of the major character are caused by defense mechanism. Defense mechanism is triggered by threatening moments. The writer finds that love, marriage and religion become major problem that make major character, Rizwan Khan produces defense mechanism. Rizwan defense mechanism leads him becomes a though man in making decision in his life.